The effect of copper sulfate and zinc oxide in a drench on the gain and health of newly arrived calves - Brazle, F.K.; Stokka, Gerald L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred and fifty-four, newly arrived, bull calves averaging 295 lb were either drenched with a copper-zinc (Cu-Zn) solution or water at arrival. The Cu-Zn drench did not affect gains during a 56-day trial. Additionally, no differences occurred in morbidity or the number of antibiotic treatments required per animal.
Keywords: Beef; Copper; Zinc; Trace minerals